Pengaruh Promosi, kepercayaan konsumen dan persepsi resiko terhadap minat beli secara online pada marketplace shopee di batam - Limbong, Ayu Neni Lestari; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2022)
This study aims to determine the effect of promotion, consumer trust and risk perceptionon buying interest partially or simultaneously. The population in this study are people wholive in Batu Aji. The number of samples taken as many as 100 people, sampling was doneusing non-probability sampling technique. The data collection method used is primary data.Data processing using SPSS Version 26 program. The results of this study indicate thatpromotion partially affects buying interest which is indicated by the t-count value of 3,396>t table1,984 and a significant value of 0.001 <0.05. Consumer confidence partially has noeffect on buying interest, which is indicated by the t count value of 1.502 < t table with1.984 and a significant value of 0.136 > 0.05. Risk perception partially has no effect onbuying interest which is indicated by the t count value of 1.588 < t table and significantvalue of 0.116 > 0.05. Promotion, consumer confidence and risk perception have asimultaneous effect on buying interest which is shown from the calculated F value of5,536 > 2.699 F table and Sig value 0.002 < 0.05. R square value of 0.129 which meansonly 0.129% there is an influence from promotion, consumer confidence and riskperception on buying interest and the remaining 9.871 is influenced by other variables thatare not variables in this study.